Analysis of structural and functional central nervous system abnormalities associated with prenatal exposure to ethanol in children of primary school age - E. V. Fadeeva; A. M. Lanovaya; A. Yu. Nenastieva; G. A. Korchagina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The article is presenting results of the third stage of the examination of primary school students for the identification and assessment of the severity of structural and functional abnormalities of the central nervous system (CNS) that arose in connection with perinatal exposure to ethanol — 77 children with previously identified delayed physical development of various degrees and characteristic dysmorphological disorders were examined. The identification of structural abnormalities to the CNS was carried out on the basis of assessing the correspondence of the occipital frontal circumference of the child’s head with the normative values for a specific sex and age, determination of functional abnormalities was carried out on the basis of an assessment of intellectual development based on the results of the Wechsler Intelligence Scale for Children and behavioral characteristics according to the Vineland Adaptive Behavior Scales.The presence of structural abnormalities to the CNS, manifested by a decrease in the occipital frontal circumference 2 or more standard deviations below the mean for the age norm, was revealed in 59 patients (77%). A serious functional disorder of the CNS, manifested by mild and moderate mental retardation, was found in 23 children (30%). Mild or moderate functional impairment of the CNS in the form of delayed cognitive development was found in 21 children (27%).Assessment of behavior and adaptive skills revealed a significant number of children (72%), whose adaptive behaviors were unfavorably different from the norm. The most common ones were: low concentration of attention — in 77%, increased anxiety and fear — in 65%, hyperactivity — in 60%, impulsivity — in 44%, outbursts of anger — in 43%, deceit and theft — in 40%, excessive dependence or codependency — in 38%, deliberate destruction of one’s own or someone else’s property — in 14% of children.Statistically significant inverse correlations of a high level of significance (p≤0.01) between indicators of nonverbal intelligence and maladaptive behavior were obtained. Inverse correlations between structural abnormalities of the CNS and nonverbal intelligence are presented at the tendency level.